Visible-light responsive hydrogen-bonded supramolecular polymers based on ortho-tetrafluorinated azobenzene. Issue 47 (21st November 2017) - Zhan, Tian-Guang; Lin, Meng-Di; Wei, Jie; Liu, Li-Juan; Yun, Meng-Yan; Wu, Lin; Zheng, Si-Tai; Yin, Huan-Huan; Kong, Li-Chun; Zhang, Kang-Da
Abstract : Visible-light responsive hydrogen-bonded supramolecular polymers have been fabricated, whose properties could be regulated through the visible-light-triggered photoisomerization of the ortho -tetrafluorinated azobenzene. Abstract : Novel visible-light responsive hydrogen-bonded supramolecular polymers have been successfully constructed by using a linear molecule, which consists of two ureido-pyrimidinone (UPy) moieties connected by a photochromic ortho -tetrafluorinated azobenzene (TFAB) linker. Benefiting from the visible-light responsive feature of the TFAB unit, reversible photoisomerization between the two isomers of the monomer can be achieved. The E -isomer prefers to form a linear supramolecular polymer through the intermolecular quadruple hydrogen bonding interactions between UPys, whereas the Z -isomer facilely forms a cyclic dimer. Therefore, the polymerization mechanisms and properties of such supramolecular polymers, e.g. reversible visible-light induced gel–sol transformation behaviour, can be regulated by the reversible visible-light triggered E / Z photo-isomerization of the TFAB chromophore.